2008
DOI: 10.3201/eid1401.070704
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Multidrug-Resistant Bacteria into the Arctic

Abstract: We show that Escherichia coli isolates originating from Arctic birds carry antimicrobial drug resistance determinants. This fi nding implies that dissemination of drug-resistant bacteria is worldwide. Resistance genes can be found even in a region where no selection pressure for resistance development exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 12 publications
2
120
2
1
Order By: Relevance
“…In case of migrating birds, resistant bacteria can be spread over large distances and even in remote areas, as Electronic supplementary material The online version of this article (doi:10.1007/s10344-017-1125-2) contains supplementary material, which is available to authorized users. multi-AMR bacteria have been found in arctic wild birds (Sjolund et al 2008). Furthermore, close contact to potentially AMR bacteria increases the liability of uptake as it was shown that Canada geese in direct contact with liquid waste had more antimicrobial resistances than those without (Cole et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In case of migrating birds, resistant bacteria can be spread over large distances and even in remote areas, as Electronic supplementary material The online version of this article (doi:10.1007/s10344-017-1125-2) contains supplementary material, which is available to authorized users. multi-AMR bacteria have been found in arctic wild birds (Sjolund et al 2008). Furthermore, close contact to potentially AMR bacteria increases the liability of uptake as it was shown that Canada geese in direct contact with liquid waste had more antimicrobial resistances than those without (Cole et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AMR has been detected, particularly among commensal gut bacteria, in wild mammals, birds, reptiles and fish, with the prevalence and resistance patterns varying across species, locations and possibly time (e.g. [3,20,[23][24][25][26][27]). Current data on AMR in wildlife largely consist of series of 'snap shots' proving the presence of resistomes (all of the antibiotic resistance genes found in microbes [13]) in those animals, but little else.…”
Section: Patterns Of Antimicrobial Resistance Infection In Wildlifementioning
confidence: 99%
“…In communal corvid roosts in Europe and the USA, 2.5-6.0% of faecal samples contained resistance genes for vancomycin, an antimicrobial 'of last resort' in human medicine [23,35]. Gulls carrying medically significant AMR are capable of long-range movements and are increasingly found feeding on anthropogenic waste and nesting in urban areas [24,27,36]. Similarly, in aquatic ecosystems, uneaten food and faeces from human sewage, agriculture and aquaculture containing antimicrobials and AMR bacteria can be ingested by wild fish and other organisms, which can travel enormous distances and in some cases enter the human food chain [20].…”
Section: Patterns Of Antimicrobial Resistance Infection In Wildlifementioning
confidence: 99%
See 2 more Smart Citations